Predictive factors for pregnancy after intrauterine insemination: A prospective study of factors affecting outcome - Mohan S Kamath; Priya Bhave; T K Aleyamma; Raju Nair; A Chandy; Ann M Mangalaraj; K Muthukumar; Korula George (Wolters Kluwer Medknow Publications, 2010)
Objective : To determine the predictive factors for pregnancy after controlled ovarian hyperstimulation (COH)/intrauterine insemination (IUI). Design : Prospective observational study. Setting : University-level tertiary care center. Patients and Methods : 366 patients undergoing 480 stimulated IUI cycles between November 2007 and December 2008. Interventions : Ovarian stimulation with gonadotrophins was initiated and a single IUI was performed 36 h after triggering ovulation. Main Outcome Measures : The primary outcome measures were clinical pregnancy and live birth rates. Predictive factors evaluated were female age, duration of infertility, indication for IUI, number of preovulatory follicles, luteinizing hormone level on day of trigger and postwash total motile fraction (TMF). Results : The overall clinical pregnancy rate and live birth rate were 8.75% and 5.83%, respectively. Among the predictive factors evaluated, the duration of infertility (5.36 vs. 6.71 years, P = 0.032) and the TMF (between 10 and 20 million, P = 0.002) significantly influenced the clinical pregnancy rate. Conclusion : Our results indicate that COH/IUI is not an effective option in couples with infertility due to a male factor. Prolonged duration of infertility is also associated with decreased success, and should be considered when planning treatment.